Overview of the Ocean Climatology and Its Variability in the Azores Region of the North Atlantic Including Environmental Characteristics at the Seabed - Amorim, Patrícia; Perán, António D.; Pham, Christopher K.; Juliano, Manuela; Cardigos, Frederico; Tempera, Fernando; Morato, Telmo (Frontiers in Marine Science, 2017)
Obtaining a comprehensive knowledge of the spatial and temporal variations of the environmental factors characterising the Azores region is essential for conservation and management purposes. Although many studies are available for the region, there is a need for a general overview of the best available information. Here, we assembled a comprehensive collection of environmental data and briefly described the ocean climatology and its variability in the Azores. Data sources used in this study included remote sensing oceanographic data for 2003-2013 (sea surface temperature, chlorophyll-a concentration, particulate inorganic carbon and particulate organic carbon), derived oceanographic data (primary productivity and North Atlantic oscillation index) for 2003-2013, and in situ data (temperature, salinity, oxygen, phosphate, nitrate and silicate) obtained from the World Ocean Atlas 2013. We have produced 78 geographic datasets of environmental data for the Azores region that were deposited at the World Data Center Pangaea and also made available at the SIGMAR Azores website. As with previous studies, our results confirmed a high spatial, seasonal and inter-annual variability of the marine environment in the Azores region, typical of mid latitudes. For example, lower sea surface temperature was found in the northern part of the study area coinciding with higher values for chlorophyll-a concentration, net primary production, and particulate organic and inorganic carbon. Higher values for some of these parameters were also found on island slopes and some seamounts. Compiled data on the environmental conditions at near-seabed revealed some notable variations across the study area (e.g. oxygen and nutrients) and with depth (e.g. temperature, salinity, and oxygen). Knowledge of these patterns will help improve our understanding of the distribution of many deep-sea organisms such as fish, cold-water corals and sponges, thereby supporting the implementation of marine spatial planning and other management measures. It should be noted, that the assembled datasets suffer from a number of limitations related to the accuracy of remote sensing and global bathymetry data, or to the limited and unevenly distributed historical environmental observations. Accordingly, an effective global network of observing systems for detecting oceanic change with adequate accuracy and precision is still required.